Beyond Administrative Labels: Brand Equity and Grassroots Understanding of Religious Moderation Villages in Indonesia - Riza Saputra; Rohana Faridah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Religious Moderation Villages (Kampung Moderasi Beragama/KMB) were established by the Indonesian Ministry of Religious Affairs as a strategic initiative to promote tolerance, social cohesion, and peaceful coexistence in religiously diverse communities. Despite widespread governmental implementation, limited evidence exists regarding how these designated villages are recognized, understood, and experienced by local residents. This study aims to examine the alignment between the official branding of Religious Moderation Villages and the actual practice and public understanding of religious moderation at the grassroots level. Employing a qualitative multiple-case study design, the research was conducted in four designated KMB locations in South Kalimantan, Indonesia. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving local government officials, religious counselors, community leaders, and residents. The analysis integrated national religious moderation indicators with brand equity perspectives, focusing on brand awareness, brand association, perceived quality, brand loyalty, and brand assets. The findings reveal a significant discrepancy between administrative designation and community recognition. While residents consistently demonstrate strong moderation practices characterized by tolerance, anti-violence, national commitment, and cultural accommodation, most participants remain unaware of their village’s formal KMB status. Weak brand awareness, limited communication strategies, insufficient visual identity, and inadequate institutional support were identified as major barriers to effective program branding. Nevertheless, strong social capital and established traditions of interfaith cooperation provide a solid foundation for strengthening the KMB identity. The study concludes that successful religious moderation initiatives require not only policy designation but also strategic communication, visible branding, and sustained community engagement to transform administrative recognition into meaningful social legitimacy and long-term program sustainability.